Knowledge of electronic medical records system among frontline health care workers in Jos University teaching hospital, Plateau State Nigeria - Afolaranmi, Tolulope O.; Hassan, Zuwaira I.; Dawar, Bulus L.; Wilson, Bamkat D.; Zakari, Abdulbasit I.; Bello, Kayode K.; Ofakunrin, Akinyemi O. D.; Ogbeyi, Gabriel O. (International Journal of Research in Medical Sciences, 2020)
Background: Electronic Medical Records system (EMRs) in any healthcare system has the potential to transform healthcare in terms of saving costs, reducing medical errors, improving service quality, increasing patients’ safety, decision-making, saving time, data confidentiality, and sharing medical. Evidence on the current state of EMR system in Nigeria health system particularly its knowledge among health professionals is limited. Hence, this study was conducted to assess the level of knowledge EMRs among frontline health care workers in a tertiary health institution in Jos, Plateau State. Methods: This was a cross-sectional study conducted between April and August 2019 among 228 frontline health care workers in Jos University Teaching Hospital using quantitative method of data collection. SPSS version 20 was used for data analysis and a p-value of ≤ 0.05 considered statistically significant. Results: The mean age of the respondents in this study was 35 ± 8 years with 93 (40.8%) being 36 years and above. The overall level of knowledge of EMRs was adjudged to be good among 163 (71.5%) of the participants. Category (pharmacists) of the respondents was found to influence good knowledge of EMRs (OR = 1.37; 95% CI = 1.007 – 1.865; p = 0.045). Conclusions: This study has demonstrated a relatively high level of good knowledge of EMRs with variation existing along the categories of health care workers bringing to light the existence of a good knowledge base in the light of future EMRs implementation.